Dukungan Keluarga terhadap Penderita Demensia di Bandung - Upik Rahmi; Yoanita Suryani (Wiraraja Medika : Jurnal Kesehatan, 2020)
Abstract Family members are primarily responsible for the care of loved ones with dementia. Family support and living with people with dementia are cultural norms that are expected in Indonesia, where family members with dementia are considered family responsibilities that must be fulfilled. The purpose of this study: to find out Family Support for Dementia sufferers. Quantitative descriptive with cross sectional design. The study was conducted in the city of Bandung with a population of 41 respondents and a sample of (n = 41) primary caregivers / families who care for dementia patients, sampling with total sampling. Family support based on education in the good category (68.3%) and not good 13 respondents (31.7%), emotional factors in the good category 26 respondents (63.4%) and not good 15 respondents (36, 6%), based on spiritual in the good category of 24 respondents (58.5%) and not good 17 respondents (43.9%), social and psychological factors are in the good category 26 respondents (63.4%) and not good 15 respondents (36.6%), and the last indicator of economic factors was in the good category of 25 respondents (61.0%) and not good 16 respondents (39.0%). Family support is very important to improve the quality of life of people with dementia, namely support based on educational, psychological / emotional, spiritual, social and environmental and economic factors. Some have provided good support, but there is still support that is not good Keywords: Dementia, Family Support, Education, Psychology